Development of Micellar HPLC-UV Method for Determination of Pharmaceuticals in Water Samples - Danielle Cristina da Silva; Cláudio Celestino Oliveira (Journal of Analytical Methods in Chemistry)
Method for extraction and determination of amoxicillin, caffeine, ciprofloxacin, norfloxacin, tetracycline, diclofenac, ibuprofen, nimesulide, levonorgestrel, and 17α-ethynylestradiol exploiting micellar liquid chromatography with PDA detector and solid-phase extraction was proposed. The usage of toxic solvents was low; the chromatographic separation of the medicaments was performed using a C18 column and mobile phases A and B containing 15.0% (v/v) ethanol, 3.0% (m/v) sodium dodecyl sulfate (SDS), and 0.02 mol·L−1 phosphate at pHs 7.0 and 8.0, respectively. The method is simple, selective, and fast, and the analytes were separated in 23.0 min. For extraction, 1000 mL of sample containing 2.0% (v/v) ethanol and 0.002 mol·L−1 citric acid at pH 2.50 was loaded through a 1000 mg of C18 cartridge. The analytes were eluted using 3.0 mL of ethanol, which were evaporated and redissolved in 0.5 mL of mobile phase. Concentration factors better than 1200, except amoxicillin (224), were obtained. The analytical curves were linear (R2 better than 0.992); LOD and LOQ n=10 presented values in the range of 0.019–0.247 and 0.058–0.752 mg·L−1, respectively. Recoveries of 99% were obtained, and the results are in agreement with those obtained by the comparative methods.